Upper Gastrointestinal Bleeding in Critically Ill Patient: Literature Review - William Faisal; Luciana Rotty (The Indonesian Society for Digestive Endoscopy, 2021)
Critically ill patients are at risk for stress ulcers in the upper digestive tract. Various risk factors have been associated with this condition. Patients who are critically ill are at risk of bleeding due to stress related mucosal disease (SRMD). Upper gastrointestinal tract problems usually occur as a result of severe physiological stress. Patients may develop gastric erosion and develop stress ulcers with severe gastrointestinal bleeding which can be fatal. Routine pharmacological use of stress ulcer prophylaxis (SUP) does not reduce overall mortality in intensive care patients. This increases the risk of infectious complications, particularly nosocomial pneumonia and Clostridium difficile-associated diarrhea. Early enteral nutrition has been shown to be effective in preventing stress ulceration of the upper gastrointestinal tract in critically ill patients. Routine use of stress ulcer prophylaxis in all critically ill patients may be dangerous and does not appear to be cost-effective. SUP administration must follow an algorithm that clearly balances risks and benefits.